Implication of Platelets in Immuno-Thrombosis and Thrombo-Inflammation - Younes Zaid; Younes Zaid; Yahye Merhi (Frontiers in Cardiovascular Medicine, 2022)
In addition to their well-described hemostatic function, platelets are active participants in innate and adaptive immunity. Inflammation and immunity are closely related to changes in platelet reactions and enhanced platelet function in thrombo-inflammation, as well as in microbial and virus infections. A platelet’s immune function is incompletely understood, but an important balance exists between its protective and pathogenic responses and its thrombotic and inflammatory functions. As the mediator of vascular homeostasis, platelets interact with neutrophils, bacteria and virus by expressing specific receptors and releasing granules, transferring RNA, and secreting mitochondria, which controls hemostasis and thrombosis, infection, and innate and adaptive immunity. This review focuses on the involvement of platelets during immuno-thrombosis and thrombo-inflammation.